A Study on Investment Behaviour of Indian Household Investors and its impact on GDP of India. - Amit Agrawal, Dr. Somesh Dhamija (International Journal of Advanced Science and Technology, 2020)
This research article is an attempt to examine relationship of Investment Behaviour of Indian Household Investors with the GDP of country. GDP is an meter of economic growth of a country, saving is a result of money spared from the consumption while investment takes place out of saving. Difference households have a different behaviour towards saving and investment based on their risk-return territory and accordingly their pattern of selecting investment avenues differ. To examine the causality among growth rate of GDP, Domestic savings, income and investment by the households, secondary data published by RBI have been collected for the period of 2005 to 2018. Regression, Correlation and Johansan co-integration test has been applied with the help of Eviews 9.0. Our findings indicate that there is positive relationship among the variables. This study is also useful for the researchers to study the impact of household investment and growth of economy and financial expert can also forecast the volatility in investment.